Analysis of Risk Factors of Non-Communicable Diseases in the Sub District of Prapatan, Balikpapan City - Fatimatuzahra, Tien; Wisnuwardani, Ratih Wirapuspita (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Non-communicable diseases (NCDs) arise from both unmodifiable risk factors, like age, gender, and genetics, and modifiable ones that can be influenced by individual and social interventions. Early detection is essential for managing risk, supported by surveillance and strategic efforts from government, private sectors, and communities. The PRAPATAN POSTER initiative at Prapatan Public Health Center provides counseling and risk assessments for NCDs in the Prapatan area Objective : To identification the risk factors of Non Communicable Diseases and correlation them in Prapatan Sub District Balikpapan City Research Methods/ Implementation Methods : This cross-sectional study used retrospective data from 363 screenings, revealing 19.3% hypertension and 7.7% diabetes prevalence. Chi-square test was tested to explore the association between age and hypertension Results : Over half (51.2%) of participants were overweight or obese, with nearly half (48.25%) reporting insufficient physical activity, and 8.5% identifying as smokers. Significant correlations were found between age and hypertension (p-value=0,000), and diabetes type 2 (p-value=0,000). A significant association was found between hypertension and obesity (p-value= 0,000). Conclusion/Lesson Learned : A significant association was found between age and hypertension and diabetes type 2. Enhancing promotive and preventive measures, as well as early interventions for prehypertensive and pre-diabetic individuals, is recommended to curb NCDs.